Recovery kinetics in soccer goalkeepers and field players - Nédélec, M.; Berthoin, S.; Dupont, G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
During a soccer match, goalkeepers and field players perform running activities and actions leading to muscle damage which may impair physical performance (Byrne et al., 2004). In addition, a soccer match induces mental activities for both goalkeepers and field players (Williams, 2000), and mental fatigue has been shown to reduce physical performance (Marcora et al., 2009). The purpose of this study was to analyze the recovery kinetics of physical and cognitive performance, as well as subjective ratings in goalkeepers and field players after a soccer match. Methods: Eight goalkeepers (age: 18.5±2.5 yr; height: 182.3±4.6 cm; body mass: 75.9±8.8 kg) and eight elite field players (17.1±0.9 yr; 180.9±5.8 cm; 70.5±6.8 kg) were tested immediately, 24 and 48h after a soccer match. The battery of test included squat jump (SJ) and countermovement jump (CMJ) on a force plate; mean power output (MPO) and mean speed (MS) during a 6-s sprint on a non-motorised treadmill; reaction and motor time during Vienna Reaction Test; number of stimuli, correct responses, incorrect responses and omitted responses during Vienna Determination Test; perceived level of recovery rating. Results: Squat Jump and CMJ were both significantly (p<0.01) decreased 24h after the match, while only CMJ remained significantly (p<0.05) lower 48h after the match. Mean power output and MS showed no change (p>0.05) for goalkeepers throughout the protocol whereas MPO and MS were significantly altered for field players immediately after the match (p<0.01). No significant interaction was found for other variables between position and time (p>0.05). There was a main effect of time (p<0.05) for fatigue and muscle soreness. Fatigue increased immediately (p<0.001) and 24h after the match (p<0.05), whereas muscle soreness was increased immediately after the match only (p<0.05). Discussion: A significant decrease in sprint was found only for field players. The different running profile of goalkeepers compared to field players (Rampinini et al., 2007; Di Salvo et al., 2008) could explain this finding. The decrement in jumps found in both goalkeepers and field players could be explained by activities leading to muscle damage (diving, tackling, changes of direction, jumps, deceleration). Results from the tests assessing some aspects of cognitive function did not show any change in goalkeepers and field players after a match.